Using Mimicry Memorization Method in Improving Student’s Learning Outcomes on the Lesson of Arabic Language - Rizqia, Ana Sabila; Sopian, Asep; Ridlo, Akhmad; Abdulkhaleq, ⁠Al-Rawafi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
The Arabic learning process is still faced with several problems, one of which is that students find it difficult to remember vocabulary and do not understand the meaning of each vocabulary. This study aims to analyze the enhancement of students’ vocabulary through the implementation of the mimicry memorization method. This study employs a quantitative approach, specifically adopting an experimental research design known as the Pre-test and post-test Control Group Design. The result of this study is that there is an increase in learning outcomes in learning Arabic vocabulary using the Mimicry Memorization method. Supported with evidence, the experimental group demonstrates an average score of 80.000, while the control group exhibits a mean score of 52.690. The results of statistical analysis showing Sig. (2-tailed) in the Independent Sample T-Test test is 0.000 0.05. These findings suggest that utilising the Mimicry Memorization technique proves to be efficacious in acquiring Arabic vocabulary.